2005
DOI: 10.1002/sat.820
|View full text |Cite
|
Sign up to set email alerts
|

Radio resource management across multiple protocol layers in satellite networks: a tutorial overview

Abstract: Satellite transmissions have an important role in telephone communications, television broadcasting, computer communications, maritime navigation, and military command and control. Moreover, in many situations they may be the only possible communication set-up. Trends in telecommunications indicate that four major growth market/service areas are messaging and navigation services (wireless and satellite), mobility services (wireless and satellite), video delivery services (cable and satellite), and interactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 90 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…Therefore, in order to provide further bandwidth adaptation flexibility in the satellite access subsystem, it is necessary to couple SDN control with the RRM functions of the satellite hub (RRM covers interface management, power control, fading mitigation, handover, admission control, congestion control, bandwidth allocation, and packet scheduling). In this case, a vertical cross-layer integrated management architecture [22] could be considered as most relevant since various OSI layers information (L1 up to L7) can be integrated in the management and control.…”
Section: Sdn-based Satellite Bandwidth On Demandmentioning
confidence: 99%
“…Therefore, in order to provide further bandwidth adaptation flexibility in the satellite access subsystem, it is necessary to couple SDN control with the RRM functions of the satellite hub (RRM covers interface management, power control, fading mitigation, handover, admission control, congestion control, bandwidth allocation, and packet scheduling). In this case, a vertical cross-layer integrated management architecture [22] could be considered as most relevant since various OSI layers information (L1 up to L7) can be integrated in the management and control.…”
Section: Sdn-based Satellite Bandwidth On Demandmentioning
confidence: 99%
“…An acceptable delivery delay is 30 s. Table 3.4 compares the applications on the basis of the service class and the associated delay requirement [8].…”
Section: Low Priority Transaction Servicesmentioning
confidence: 99%
“…The hybrid ARQ is a classic example of a cross-layer approach, where end to end data reliability is provided by a combination of the physical layer, data link layer, and transport layers [4]. The authors in Reference [2] conducted a numerical analysis of the cross layer integration of adaptive modulation and coding (AMC) with ARQ over a terrestrial wireless channel, and revealed that retransmissions in the data link layer relieve stringent error control requirements at the physical layer.…”
Section: Introductionmentioning
confidence: 98%
“…Mobile satellite systems will be fully integrated within 4G systems, playing important roles in the areas where terrestrial communications infrastructure is very expensive and impractical or satellite communications may be the only solution, due to the wide area coverage, reconfigurability, and multicast capabilities [4]. In this sense, maintaining the compatibility with terrestrial systems is another important issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation